The Effects of “Ceria” Chemotherapy Effect Management on the Life Quality Improvement of Children with Cancer - Siti Lestari; Sri Hartini Mardi Asih; Rusmiyati Rusmiyati (GLOBAL HEALTH SCIENCE GROUP, 2019)
The prevalence of cancer in children is now increasing and followed by an increasing number of them who undergo chemotherapy. The effect of chemotherapy can reduce the children’s quality of life, hence it requires the contribution of nurses in improving health services to children with cancer. The purpose of the study was to analyze the effect management of “Ceria” chemotherapy : (C)egah Sariawan (preventing mucositis), Cegah (E)kstravasasi (preventing extravacation), (R)elaksasi (Progressive Muscle Relaxation to reduce fatigue), Cegah (I)nfeksi (preventing infection), (A)kupresur (acupressur to reduce nausea and vomiting) on the life quality of children with cancer. The method applied was experimental research using control group design with pretest posttest. The treatment group received intervention in the form of “Ceria” chemotherapy effect management from the researchers while the control group did not receive intervention treatment. The selection of research subjects for the treatment and control groups was done randomly. The children’s quality of life was measured before and after one week of intervention using PedsQL (Children's Quality of Life Inventory). The participants were 76 children (38 in the treatment group and 38 in the control group). The results of the paired t test showed that there were significant mean differences of life quality before and after